Effectiveness of neem seeds extract to control diamondback moth (Plutella xylostella) - Brotodjojo*, Rukmowati (Jurnal Agrivet, 2014)
Synthetic insecticides have detrimental effect to environment. Botanical insecticides are considered to be safer to the environment. Need seeds contain compounds with insecticidal properties. The aim of this study was to examine the effectiveness of neem seeds extract to control Diamondback moth (DBM). A series of neem seeds extract concentration (0.04 %, 0.08 %, 0.16 %, 0.32 %) and control (without neem extract) were tested on second instar larvae in oral test and contact test. The results showed that neem seeds extract have significant effect on the mortality of second instar DBM larvae 24-72 h after treatment in oral test and 72 h after treatment in contact test. In the oral test, the neem seeds extract significantly reduced feeding intensity of the larvae 42 h and 72 h after treatment. Subsequently, the extract also significantly reduced the moth emergence. The neem seeds with concentration 0.16 % effectively control DBM second instar larvae 72 h after treatment. Insektisida sintetis memiliki efek merugikan bagi lingkungan. Insektisida botani dianggap aman untuk lingkungan. Biji nimba mengandung senyawa dengan sifat insektisida. Tujuan dari penelitian ini adalah untuk mengetahui efektivitas ekstrak biji nimba untuk mengendalikan ulat kobis Plutella xylostella. Serangkaian konsentrasi ekstrak biji nimba (0,04%, 0,08%, 0,16%, 0,32%) dan kontrol (tanpa ekstrak nimba) diuji pada larva instar kedua dengan uji pakan dan uji kontak. Hasil penelitian menunjukkan bahwa ekstrak biji nimba berpengaruh nyata terhadap mortalitas larva instar II 24-72 jam setelah perlakuan pada uji pakan dan 72 jam setelah perlakuan pada uji kontak. Pada uji pakan, ekstrak biji nimba secara nyata mengurangi intensitas makan larva 42 jam dan 72 jam setelah perlakuan. Selanjutnya, ekstrak juga secara nyata mengurangi munculnya ngengat. Ekstrak biji nimba dengan konsentrasi 0,16% efektif mengontrol ulat kobis instar kedua 72 jam setelah perlakuan.